Checklist of water bugs (Hemiptera: Heteroptera: Nepomorpha, Gerromorpha) of Slovakia - Klementová, Barbora Reduciendo; Kment, Petr; Svitok, Marek (Zootaxa, 2015)
The water bugs represent a significant component of the freshwater biota, play an important role in trophic webs, and may have considerable economic importance. Nevertheless, systematic research of this group has been underdeveloped in Slovakia (central Europe) for decades. This work presents a list of water bug species of Slovakia based on an exhaustive review of the literature (time span: 1808–2013) and on more than 14,000 individuals collected during extensive field campaigns (2010–2014) or obtained from insect collections. Fifty-six species belonging to 11 families of Heteroptera were recorded from a total of 767 sites. Seven species were recorded for the first time from Slovakia during our research. Among those, the first exact records of Corixa panzeri Fieber, 1848, Sigara (Subsigara) distincta (Fieber, 1848), Notonecta (Notonecta) lutea Müller, 1776, Notonecta (Notonecta) maculata Fabricius, 1794 and Microvelia (Microvelia) buenoi Drake, 1920 are provided here. Confusion concerning the records of two additional species, Arctocorisa carinata carinata (C. R. Sahlberg, 1819) and Hesperocorixa parallela (Fieber, 1860) is clarified. The water bugs species inventory appears to be nearly complete (~97 %) given an asymptotic richness estimate. The occurrence of other species is discussed taking into account their habitat requirements and distribution in neighbouring countries. Recommendations for future research are provided.